Childhood trauma is not a confounder of the overlap between autistic and schizotypal traits: A study in a non-clinical adult sample. (November 2017) - Gong, Jing-bo; Wang, Ya; Lui, Simon S.Y.; Cheung, Eric F.C.; Chan, Raymond C.K.
Abstract: Childhood trauma has been shown to be a robust risk factor for mental disorders, and may exacerbate schizotypal traits or contribute to autistic trait severity. However, little is known whether childhood trauma confounds the overlap between schizotypal traits and autistic traits. This study examined whether childhood trauma acts as a confounding variable in the overlap between autistic and schizotypal traits in a large non-clinical adult sample. A total of 2469 participants completed the Autism Spectrum Quotient (AQ), the Schizotypal Personality Questionnaire (SPQ), and the Childhood Trauma Questionnaire-Short Form. Correlation analysis showed that the majority of associations between AQ variables and SPQ variables were significant ( p < 0.05). In the multiple regression models predicting scores on the AQ total, scores on the three SPQ subscales were significant predictors( P s < 0.05). Scores on the Positive schizotypy and Negative schizotypy subscales were significant predictors in the multiple regression model predicting scores on the AQ Social Skill, AQ Attention Switching, AQ Attention to Detail, AQ Communication, and AQ Imagination subscales. The association between autistic and schizotypal traits could not be explained by shared variance in terms of exposure to childhood trauma. The findings point to important overlaps in the conceptualization of ASD and SSD, independent of childhood trauma. Highlights: The present study have a large non-clinical adult sample. These findings are important for informing the relation of trauma to ASD and SSD. Childhood trauma is not a confounder of the relationship between autistic and schizotypal traits.